Association between Non-Suicidal Self-Injury, Parents and Peers Related Loneliness, and Attitude Towards Aloneness in Flemish Adolescents: An Empirical Note. Issue 1 (20th February 2018) - Gandhi, Amarendra; Luyckx, Koen; Goossens, Luc; Maitra, Shubhada; Claes, Laurence
Loneliness and attitude towards aloneness have been shown to be associated to depression, anxiety, and other psychiatric disorders in adolescents and they may also increase the vulnerability to Non-Suicidal Self-Injury (NSSI). Therefore, the present study investigated the association between lifetime prevalence and functions of NSSI, parent- and peer-related loneliness, and attitude towards aloneness (positive and negative). Data regarding NSSI, loneliness, and attitude towards aloneness were collected from a sample of 401 high school students from three different high schools located in the Dutch-speaking part of Belgium. Lifetime prevalence of NSSI was found to be 16.5%. Females reported a higher lifetime prevalence of NSSI than males. Higher mean scores for parent-, peer-related loneliness, and positive attitude (i.e., affinity) towards aloneness was observed in adolescents with lifetime NSSI as compared to adolescents without a history of NSSI. Finally, a positive correlation between self-related (i.e., automatic) functions of NSSI and parent- and peer-related loneliness and a positive attitude towards aloneness was also observed.